EFFECT OF COMBINATION OF DILL AND YOGURT ON GROWTH PERFORMANCE AND SOME PHYSIOLOGICAL TRAITS IN LOCAL QUAILS - Lanja A. Ismael,; Payam Sadik Sabir, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The current study aimed to determine the effect of adding mixture of dried dill (Anethum gravelens) powder at levels 0.2 % with yogurt to the quail diet on the productive and physiological characteristics of male and female quails. The experimental birds were divided into four treatments, and each treatment was divided into three replicates, with 8 birds for each replicate. The results showed a significant superiority of quail birds in the fourth treatment in the body weight at 42 days (210.08±3.34 g/bird), carcass weight (125.50±1.9 g/bird), highest value of HDL (14.50 ± 0.33 mg/dL) and the number of white blood cells (123.21 ± 5.66100/µL). While the birds of the second treatment excelled in the hemoglobin ratio in the blood (22.50 ± 0.31 g/dL) and recorded the lowest percentage of total cholesterol (188.63 ± 47 mg/dL) and the lowest LDL value (22.58 ± 1.66 mg/dL). Female quail were significantly superior in body and carcass weight at 42 days of age, while males were superior to females in most of the physiological traits studied. Brown quails also significantly outperformed white quails in body weight at 42 days (215.52 ± 4.83 g/bird), carcass weight (127.66 ± 2.33 g/bird), and white blood cell count (120.49 ± 4.16µL/100).